2021
DOI: 10.1080/09553002.2020.1859155
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low dose and low dose rate low linear energy transfer radiation on animals – review of recent studies relevant for carcinogenesis

Abstract: Purpose: Carcinogenic effects of radiation are often assumed to be universally understood, more often than, for example, carcinogenic effects of many different chemicals. This in turn leads to an assumption that any dose of radiation, delivered at any dose rate, poses a serious health challenge. This remains an issue of dispute and low dose radiation research is focused on understanding whether these exposures contribute to cancer incidence. This review is focused on the low linear energy transfer (low LET) ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…Second, the animals were radiated by low-dose gamma rays which do not represent space radiation. Ground-based low-dose gamma or x-ray radiation studies are often used to study the effect of space-relevant radiation exposures (in terms of total dose) on different tissues/systems 6 , 47 , 48 as to inform future space radiation experiments and form an initial understanding of the impacts across radiation doses and types. However, further studies should be implemented with higher dose gamma radiation and GCR simulations to leverage a more realistic space radiation analog.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the animals were radiated by low-dose gamma rays which do not represent space radiation. Ground-based low-dose gamma or x-ray radiation studies are often used to study the effect of space-relevant radiation exposures (in terms of total dose) on different tissues/systems 6 , 47 , 48 as to inform future space radiation experiments and form an initial understanding of the impacts across radiation doses and types. However, further studies should be implemented with higher dose gamma radiation and GCR simulations to leverage a more realistic space radiation analog.…”
Section: Discussionmentioning
confidence: 99%
“…The highest dose rate is observed for the Mark I-68, while being ∼40% lower for the X-Rad320 at 320 kVp. It has been shown that dose rates play an important role in the biological effects of radiation (Hall and Brenner 1991, Rühm et al 2016, Brooks et al 2016, and, in particular, for small animal irradiation (Down et al 1991, Paunesku et al 2021. Furthermore, high energy photons deliver more dose per photon and unit of length, being higher for 137 Cs than for x-rays (figure 9).…”
Section: Comparison Between 137 Cs and Medium-energy X-ray Irradiationmentioning
confidence: 99%
“…Ionizing radiation is used to treat cancer [ 1 , 2 ], but is also a carcinogen [ 3 , 4 ]. Alongside that, there has been mounting interest not only in radiotherapy for non-cancer diseases [ 5 , 6 , 7 , 8 , 9 ], but also the non-cancer effects of radiation exposure that occur at doses or dose rates much lower than previously suggested or considered [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%